Performance-influencing factors in homogeneous groups of top athletes: a cross-sectional study - van Ingen Schenau, G. J.; de Koning, J. J.; Bakker, F. C.; de Groot, G. (Medicine & Science in Sports & Exercise, 1996)
Sport scientists have identified many factors as prerequisites for a good athletic performance in various sports. It is not clear whether these factors also influence the best performers in the homogeneous groups of top athletes selected for national teams. In this study, this issue is addressed with members of the Dutch National Junior Speed Skating Team. A total of 237 different technical, physiological, anthropometrical, and psychological parameters were collected, including many that correlated with performance in previous studies. High speed film analyses during the National Championships provided the technique parameters. A 30-s sprint test and a 150-s supramaximal test on a cycle ergometer underlie the physiological data, and questionnaires were used to measure personality traits and emotional feelings. Only trunk position and the direction of push-off (push-off angle phi) correlated consistently with skating performance in this group (r = 0.61-0.73 and r = -0.65 to -0.70, respectively). The small number of meaningful correlations means that sport scientists will have to develop more reliable methods, models, and theories to contribute significantly to knowledge useful to top athletes and their coaches.